Dynamic characteristics of polymeric foam materials under low speed - high impact energy using Dynatup 825CF / Kyairul Anuas Mohd and Mohamad Noraini Mansor - Mohd, Kyairul Anuas; Mansor, Mohamad Noraini (2000)
This project study mainly concerns on the study of the dynamic characteristics of polymeric foam materials as an impact energy absorbent medium. Experimentation procedures conducted should be treated as the preliminary stages towards gaining sufficient information before the simulation of the dynamic behaviour of foam materials is possible (the simulation part will be performed by the next group of researchers using Simulink - a, compliment software of Matlab.